Decreased Pituitary Height and Stunted Linear Growth After Radiotherapy in Survivors of Childhood Nasopharyngeal Carcinoma Cases - Xie, Chuanbo; Li, Jiaoxing; Weng, Zijin; He, Long-Jun; Yin, Shaohan; Zhang, Jingwen; Zhang, Jing; Sun, Tao; Li, Haojiang; Liu, Yuying (Frontiers in Endocrinology, 2018)
To examine the morphological changes of the pituitary glands and linear growth of childhood nasopharyngeal carcinoma (NPC) cases who accepted radiotherapy. A total of 90 children (i.e., age less than 18 years) who were diagnosed as NPC at Sun Yat-sen University Cancer Center from January 2009 to January 2015 were identified by reviewing medical records. Two radiologists reviewed and measured the pre-radiation, post-radiation, and the latest available pituitary gland heights independently. Patients’ current height information was collected by telephone interviews. We compared the pituitary height differences using paired t-tests and estimated the pituitary height trajectories within each sex by mixed regression models. Height-for-age Z-score was calculated for each patient using the WHO growth reference data for 5-19 years as reference. Most of the included participants were of male sex (75.6%) and over half were diagnosed at stage IV (58.4%). Among the 90 included participants, 89 had one repeated measurement of the pituitary height and 79 had two repeated measurements of the pituitary height. Seventy six of the 89 childhood NPC participants had reduced pituitary heights after radiation and accounted for 85.4% of the whole population. The means of the pituitary heights before and after radiotherapy were 6.4±1.3 mm and 5.6 ±1.2 mm (P<0.001), respectively. The mean of height-for-age Z-score for childhood NPC cases was significantly below zero (-0.54, 95% CI= -0.74, -0.34). We concluded that childhood NPC cases had decreased pituitary heights and stunted linear growths after radiotherapy.